Location Analysis of City Public Transport Shelters in Commercial Corridors (Case Study: Jl. Dr. Wahidin, Pekalongan City) - Ardiana Yuli Puspitasari; Eko Arief Budiarto; Rachmat Mudiyono (Universitas Islam Sultan Agung, 2021)
Dr. Wahidin Street is one of the important corridors in Pekalongan City and passed by the city's public transportation. When viewed the arrangement of land use in the vicinity, this corridor is dominated by trade, services, housing, education, and office activities. This makes the potential for population attraction and movement using public transportation modes in this road corridor relatively large. However, along the corridor, currently, only 1 (one) shelter is available, and it is rarely used by passengers. The main reason is that the distance to the existing shelter is too far. Currently, passenger boarding and disembarking activities are still carried out in any place so that they often obstruct traffic flow and endanger passengers. The purpose of this study is to determine the number and location of shelters to accommodate the needs of passengers in the corridor of Dr. Wahidin Street, Pekalongan. The analysis method in this research is a quantitative analysis using the Set Covering Problem and analysis tools using ArcGis and Lingo 8.0 software. The results showed that the number of shelters needed was 4 (four) units with 2 locations each in the West of the road (Dr. Wahidin Shelter and in front of PPIP Wholesale Market) and 2 in the East of the road (around the Pandu Shop and the Honda Dealer).